Color Preferences of Patients Receiving Elastic Ligatures - Elekdag-Turk, Selma; Ozkalayci, Nurhat; Isci, Devrim; Turk, Tamer (European Journal of Dentistry, 2010)
Objectives: To determine the color preferences for elastic ligatures among patients receiving fixed-appliance orthodontic therapy.Methods: Five hundred patients with metal brackets (336 female patients and 164 male patients) were included, and their color preferences for elastic ligatures were recorded using a color scale. Chi-square analysis was performed to evaluate the color preferences and to determine the influence of age and gender on color preferences (P<.05).Results: Two hundred and seventy-six patients (55.2%) preferred strikingly colorful elastic ligatures, while 224 patients (44.8%) preferred less noticeable elastic ligatures. No significant difference was observed between the color preferences of female and male patients (P>.05). However, significant differences were observed between the color preferences of adolescents and older patients (P<.001).Conclusions: Female patients preferred red–purple-colored tones, while male patients preferred blue–black-colored tones. Adolescents preferred colorful elastic ligatures, while older patients preferred ligatures with less-noticeable colors. A stock of 10–12 colorful and less-noticeable elastic ligatures seems to be adequate to ensure patient satisfaction. (Eur J Dent 2010;4:171-174)
Keywords: Color preference; Elastic ligatures; Orthodontic therapy